2023
DOI: 10.1038/s42003-023-04470-5
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of N- and C-terminal substrate transmembrane domain segments in intramembrane proteolysis by γ-secretase

Abstract: Intramembrane proteases play a pivotal role in biology and medicine, but how these proteases decode cleavability of a substrate transmembrane (TM) domain remains unclear. Here, we study the role of conformational flexibility of a TM domain, as determined by deuterium/hydrogen exchange, on substrate cleavability by γ-secretase in vitro and in cellulo. By comparing hybrid TMDs based on the natural amyloid precursor protein TM domain and an artificial poly-Leu non-substrate, we find that substrate cleavage requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…The authors conclude that flexibility in N-terminal part as well as in the hinge region promotes efficient cleavage. Flexibility in the C-terminal part of the substrate was suggested to allow for the formation of a cleavage-competent state near the active site [119]. These observations are in our opinion in line with the unwinding model [72,134] and nicely correlate with the data on TNFa and SPPL2a [101].…”
Section: Processivitysupporting
confidence: 85%
See 2 more Smart Citations
“…The authors conclude that flexibility in N-terminal part as well as in the hinge region promotes efficient cleavage. Flexibility in the C-terminal part of the substrate was suggested to allow for the formation of a cleavage-competent state near the active site [119]. These observations are in our opinion in line with the unwinding model [72,134] and nicely correlate with the data on TNFa and SPPL2a [101].…”
Section: Processivitysupporting
confidence: 85%
“…For SPPL3, it was suggested that an M or Y in position P1 might be favorable [33]; however, a recent N‐terminomics study on the enzyme did not detect a consensus sequence [118]. Yet, the authors found that when substrate and SPPL3 are located in the same compartment, the exchange of the TM domain can turn a nonsubstrate to a substrate [119]. They conclude that despite the lack of a clear consensus sequence structural properties of the TM domain determine cleavability.…”
Section: Cleavage Mechanisms Of Aspartyl Intramembrane Proteasesmentioning
confidence: 99%
See 1 more Smart Citation
“…As negative controls we included the TMDs of the nonsubstrate ITGB1 and a synthetic TMD consisting of 21 leucines (poly leucine 21, pL21, same number of amino acids as in the FN14 TMD), which has a strongly reduced conformational flexibility and prevents γsecretase cleavage, as shown for the substrate C99. 13 Full-length proteins in the lysate and the secreted peptides in the conditioned medium were detected on the same membrane by immunoblot using an anti-HA antibody. Immunoblot intensity of the secreted peptides were quantified and normalized to the intensity of the corresponding full-length protein to control for potential differences in transfection efficiency or protein expression.…”
Section: The Transmembrane Domain Sequence Determines the Cleavage Ef...mentioning
confidence: 99%
“…11 γ-Secretase does not cleave with a pronounced sequence specificity, but may rather require structural flexibility within a substrate's TMD. [12][13][14] Additionally, membrane proteins require a short extracellular domain (ectodomain) to be recognized and cleaved by γsecretase. [15][16][17] This prevents most known γsecretase substrates from being constitutively cleaved, because they have long ectodomains.…”
Section: Introductionmentioning
confidence: 99%